2017
DOI: 10.1002/jsfa.8499
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different home‐cooking methods on textural and nutritional properties of sweet potato genotypes grown in temperate climate conditions

Abstract: Traditional and new sweet potato cultivars can be cultivated in temperate climate conditions and show interesting qualitative properties, especially as a result of the presence of antioxidant compounds. Concerning global quality, colored varieties expressed a better profile than traditional Italian ones and they are suitable for the European market, giving new opportunities for consumers and producers. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 43 publications
6
25
0
Order By: Relevance
“…The data concerning sweet potatoes are shown in Table 3. The nutritional constituents evaluated in this vegetable were β-C, which represents the main carotenoid in orange-fleshed sweet potatoes [36], and TP, mainly represented by the phenolic acids in the orange-flesh roots [7,37]. The solid content of the sweet potatoes used in this research was 18.3 and 19.2 g/100 g for the two lots, respectively, which is lower than what is reported in the literature [7,38].…”
Section: Sweet Potatoesmentioning
confidence: 56%
See 4 more Smart Citations
“…The data concerning sweet potatoes are shown in Table 3. The nutritional constituents evaluated in this vegetable were β-C, which represents the main carotenoid in orange-fleshed sweet potatoes [36], and TP, mainly represented by the phenolic acids in the orange-flesh roots [7,37]. The solid content of the sweet potatoes used in this research was 18.3 and 19.2 g/100 g for the two lots, respectively, which is lower than what is reported in the literature [7,38].…”
Section: Sweet Potatoesmentioning
confidence: 56%
“…Conversely, an enhancement of carotenoids bioavailability in cooked carrots and spinach, attributed to the ease of chemical extraction after cooking, was evidenced [5]. In general, many studies showed that all cooking methods improve some while compromising other nutritional and technological aspects of food (e.g., the leaching of soluble vitamins), suggesting that methods not requiring water immersion help to preserve the nutritional value of the product [7,8]. Another study, which focused on the color, pigments, total phenolic content and antioxidant activity in artichokes, green beans, broccoli and carrots cooked under different conditions, indicated that sous-vide cooking preserved chlorophyll, carotenoids, phenolic content and antioxidant activity to a greater extent than boiling and retained color better [9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations